A Comparative Analysis Of Vikor And Topsis For Scholarship Selection - Kanti Lestari; Muhammad Brilliant; Dwi Handoko (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Scholarships can be interpreted as financial assistance given to students who have achievements and economic limitations. Selection of scholarship recipients atSTMIK Pringsewu still uses manual selection. Manual selection has a weakness in making selections using many criteria, so that it can lead to errors and inconsistentassessments. This study uses the VIKOR method as a ranking method for determining scholarship recipients with criteria set by the leadership, namely: Achievement Index, semester, electric power and home electricity bills. The VIKOR method is a Multi-Criteria Decision Making (MCDM) method that can be used to select more than one criteria. The VIKOR method focuses on ranking by compromising on alternative outcomes and conflicting criteria. The results showed that the VIKOR method can assist the selection process and determine the right scholarship recipient. In addition, the VIKOR method can create a ranking of alternative compromises from a number of existing alternatives Keywords— Scholarship, VIKOR, MADM, MCDM